THE SYNERGISTIC EFFECT OF HIGH BMI AND LOW PHYSICAL ACTIVITY ON GOUT ARTHRITIS RISK: A CASE -CONTROL STUDY IN WEST SUMATERA INDONESIA - Widhiastuti, Erma; Huda, Mega Hasanul; Susanto, Herry; Kurniasari, Maria Dyah; Putra, Hasriza Eka (Fakultas Kesehatan Universitas Muhammadiyah Sumatera Barat, 2025)
Background: A body mass index (BMI) of 24.9 kg/m² is a well-established risk factor for gout arthritis. However, the combined effect of obesity and decreased physical activity on the prevalence of gout arthritis in West Sumatra, Indonesia, remains unclear. This study aimed to investigate the relationship between obesity and its synergistic effect with decreased physical activity in increasing the risk of gout arthritis. Methods: A case-control study was conducted with 105 participants recruited from a health center in West Sumatra, Indonesia. Participants were divided into two groups: healthy controls (n=57) and gout arthritis patients (n=48). Physical activity levels were assessed using the modified Physical Activity Guidelines from the Advisory Committee for Americans and quantified as metabolic equivalent of task (MET)-hours per week over a 12-month period. BMI was measured by weight in kilograms divided by the square of their height in meters. Logistic regression analysis was used to determine the associations. Results: Participants with a BMI ≥ 24.9 kg/m² were 4.78 times more likely to develop gout arthritis compared to those with a BMI 24.9 kg/m² (Adjusted Odds Ratio [AOR] = 4.78; 95% Confidence Interval [CI] = 1.73–13.23; p 0.01). Additionally, those engaging in lower physical activity ( 7.5 MET-hr/week) were 3.35 times more likely to develop gout arthritis compared to those with higher levels (AOR = 3.35; 95% CI = 1.06–10.53; p 0.05). Conclusions: In West Sumatra, Indonesia, obesity (BMI 24.9 kg/m²) and its synergistic interaction with decreased physical activity significantly contribute to the increased risk of gout arthritis. Public health interventions addressing both weight management and promotion of physical activity are essential for reducing the disease burden.